Accuracy of a new electronic nose for prostate cancer diagnosis in urine samples. (9th May 2022) - Taverna, Gianluigi; Grizzi, Fabio; Tidu, Lorenzo; Bax, Carmen; Zanoni, Matteo; Vota, Paolo; Lotesoriere, Beatrice Julia; Prudenza, Stefano; Magagnin, Luca; Langfelder, Giacomo; Buffi, Nicolò; Casale, Paolo; et al.
Abstract : Objective: To evaluate the accuracy of a new electronic nose to recognize prostate cancer in urine samples. Methods: A blind, prospective study on consecutive patients was designed. Overall, 174 subjects were included in the study: 88 (50.6%) in prostate cancer group, and 86 (49.4%) in control group. Electronic nose performance for prostate cancer was assessed using sensitivity and specificity. The diagnostic accuracy of electronic nose was reported as area under the receiver operating characteristic curve. Results: The electronic nose in the study population reached a sensitivity 85.2% (95% confidence interval 76.1–91.9; 13 false negatives out of 88), a specificity 79.1% (95% confidence interval 69.0–87.1; 18 false positives out of 86). The accuracy of the electronic nose represented as area under the receiver operating characteristic curve 0.821 (95% confidence interval 0.764–0.879). Conclusions: The diagnostic accuracy of electronic nose for recognizing prostate cancer in urine samples is high, promising and susceptible to supplemental improvement. Additionally, further studies will be necessary to design a clinical trial to validate electronic nose application in diagnostic prostate cancer nomograms.